EVALUASI KEPATUHAN PERLAKUAN AKUNTANSI ASET TETAP ENTITAS TERHADAP PSAK 16 PT. FM - Marsha Adelia Yolina; Nurika Restuningdiah; Diantoro Tanner Kusuma Than (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya, 2026)
One of the factors that influence the success of a company's operations is assets. The larger the company grows, the more assets are needed for its smooth operations. Fixed assets must be managed to maximize operational benefits and ensure investment funds are in accordance with regulations. This study aims to review and analyze the application of fixed asset accounting at PT. Filtrona Manufacturing Indonesia by referring to the provisions of PSAK No. 16. One of the problems that still often occurs is that the measurement and disclosure of assets are not in accordance with PSAK No. 16. This study applies a qualitative approach with a descriptive method to obtain a more comprehensive understanding of the actual condition of the accounting system in the object studied. The main data is primary data obtained through interviews and direct observation in the company environment. Interview subjects were selected using a purposive technique to ensure the data obtained are relevant and significant. The research findings indicate that the accounting treatment of fixed assets at PT. Filtrona Manufacturing Indonesia is in accordance with the provisions stipulated in PSAK No. 16.